The significant relationship among factors contributing towards customer satisfaction at Y-Centre, UTC Melaka / Siti Yuwanis Zainal Abidin - Zainal Abidin, Siti Yuwanis (Faculty of Business and Management, 2017)
The purpose of this research was to determine the significant relationship among resource, outcomes, process and image and social responsibility towards customer satisfaction at Y-Centre, Melaka. There were four objectives in this research: 1) to investigate whether resource has positive relationship with the customer satisfaction, 2) to examine whether outcomes has positive relationship with the customer satisfaction, 3) to study whether process has positive relationship with the customer satisfaction and 4) to determine whether image and social responsibility has positive relationship with the customer satisfaction. The quantitative research approach was in this study as a research design. The study samples is 112 customers of Y-Centre, Melaka as the case study. Data analysis for this study was conducted using SPSS (Statistical Package for the Social Sciences) software. The analysis used descriptive statistics such as mean, frequency, percentage and standard deviation, as well as correlation analysis and regression analysis to facilitate meaningful analysis. The findings indicated that there were significant relationships between resource, outcomes, process, image and social responsibility and customer satisfaction.